Revalorizações versus conservadorismo contabilístico: evidência das entidades nacionais cotadas e não cotadas - Martins, Natália Isabel Pacheco (2021)
Accounting conservatism follows the history of accounting through the principle of prudence. Although this is not included in the International Accounting Standard Board (IASB's) Conceptual Framework for Financial Reporting 2018, there are several features in accounting standards that show conservatism is present, relying on the argument that its use brings benefits to the various economic agents. Both within the Accounting Standardization System (SNC) and International Financial Reporting Standards (IFRS), entities may opt for the revaluation model for the subsequent measurement of tangible and intangible fixed assets, which gives rise to the recognition of revaluation surpluses. In this way, the company becomes less conservative, because, from the outset, a company manages to update the value of its assets to higher values, which does not happen in the presence of conservatism. Thus, in this study, revaluations were applied as a negative proxy for conservatism. The main objective of this work is to analyze the determinants of accounting conservatism based on the practice of revaluations. The development of this work is essentially related to the scarcity in the literature with regard to empirical evidence related to revaluations in small and medium-sized national entities. Thus, 44 Portuguese companies were analyzed (main sample), of which 32 are small and medium-sized unlisted entities (sub-sample) and the remaining 12 companies are listed on the stock exchange (sub-sample) in the period between 2010 and 2019. The empirical model was based on the model of Astami and Tower (2006), with six regressions estimated in a panel data. Empirical results show that revaluations are more significant in listed entities than in unlisted entities. Furthermore, revaluations showed a downward trend, consistent with Portuguese companies' conservative accounting practices. In the analysis of the determinants of revaluations, only indebtedness and company size have a significant effect, with both determinants being negatively associated with revaluations.